Intelligent map guider / Vikneswaran Veerasamy - Vikneswaran, Veerasamy (2004)
The Intelligent Map Guider is an Internet based system which has a concept of multimedia in presenting the information in an interactive way trought the website. This system concentrates on the PUTRA LRT system. It guides the user to the destination and displays information regarding the PUTRA stations and services provided by them. There are 25 PUTRA stations and each station has it own unique destination which is either tourist attraction or public attraction. Intelligent Map Guider is developed to exploit the unique and the speciality of the tourist and public destination surrounding the PUTRA station for the tourist and public through an interactive virtual tour. Waterfall model with prototyping approach is selected for the development of this Intelligent Map Guider. This method is adopted because it is easy to understand, secondly it is easily described and finally it is easy to be implemented. In addition management of each phase in waterfall mode with prototyping is divided clearly.Intelligent Map Guider is fully developed using Macromedia tools and 3D studio Max to enhance the graphics for the virtual tour. The Dreamweaver is used for the Internet browser and finally the system is equipped with high-end Microsoft 2000 database using Microsoft Access 2000 for the ticketing database. Finally, the database is linked to the web page using Active Service Provider (ASP). Soft system methodology is adopted through the system development life cycle to understand the current problem situation. The system requirements are identified, translated into design and finally implemented into coding. The completed system is evaluated to meet the system requirement specification.